Side affects : on being trans and feeling bad - Malatino, Hil (University of Minnesota Press, 2022)
"This manuscript productively joins affect theory and trans studies to examine how narratives around gender transition actually reinforce racial and gender hegemonies. Malatino notes that trans structures of feeling are ofted coded as negative, on both sides of the transition... When a trans person wants to transition, discourses around negativity, such as childhood trauma and the 'wrong body'. Post-transition, the lives of trans people, especially trans people of color, are seen as victims of a violent society. Malatino's manuscript works slowly through the negative affect that so often shapes trans lives to consider its productive dimensions, where negativity is key to enabling trans survival and flourishing."--